2023
DOI: 10.3390/molecules28155624
|View full text |Cite
|
Sign up to set email alerts
|

Apitherapy in Post-Ischemic Brain Neurodegeneration of Alzheimer’s Disease Proteinopathy: Focus on Honey and Its Flavonoids and Phenolic Acids

Abstract: Neurodegeneration of the brain after ischemia is a major cause of severe, long-term disability, dementia, and mortality, which is a global problem. These phenomena are attributed to excitotoxicity, changes in the blood–brain barrier, neuroinflammation, oxidative stress, vasoconstriction, cerebral amyloid angiopathy, amyloid plaques, neurofibrillary tangles, and ultimately neuronal death. In addition, genetic factors such as post-ischemic changes in genetic programming in the expression of amyloid protein precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 224 publications
(465 reference statements)
0
4
0
Order By: Relevance
“…In vivo findings have shown that p-CA supplementation diminishes the degeneration of axon in sciatic nerves of rat and OS, followed by ischemia or reperfusion [136]. p-CA has also exhibited neuroprotective potential in models of global and local cerebral ischemia by preventing apoptosis and ROS generation [137].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…In vivo findings have shown that p-CA supplementation diminishes the degeneration of axon in sciatic nerves of rat and OS, followed by ischemia or reperfusion [136]. p-CA has also exhibited neuroprotective potential in models of global and local cerebral ischemia by preventing apoptosis and ROS generation [137].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…On the other hand, older patients show a marked decline in overall performance between 6 and 30 months poststroke [ 29 ]. According to recent projections, by 2030, the number of stroke survivors is predicted increase to 77 million [ 10 , 30 , 31 ]. Despite this, the global death rate due to cerebral ischemia has decreased significantly [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the global death rate due to cerebral ischemia has decreased significantly [ 12 ]. If these global stroke trends continue, by 2030 there is predicted to be approximately 70 million stroke cases, approximately 12 million deaths and more than 200 million disability-adjusted life years annually [ 30 , 31 ]. Despite significant progress in the diagnosis and treatment of brain ischemia, it is assumed that around 2050, the number of brain ischemia cases is likely to double, and disability after stroke is predicted to also increase due to the increasing number of patients whom are likely to survive an ischemic episode [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation